2016
DOI: 10.1103/physrevb.93.104414
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure, magnetoelastic coupling, and thermal properties ofEuCrO3nanopowders

Abstract: We carried out detailed studies of the magnetic structure, magnetoelastic coupling, and thermal properties of EuCrO3 nano-powders from room temperature to liquid helium temperature. Our neutron powder diffraction and X-ray powder diffraction measurements provide precise atomic positions of all atoms in the cell, especially for the light oxygen atoms. The low-temperature neutron powder diffraction data revealed extra Bragg peaks of magnetic origin which can be attributed to a Gx antiferromagnetic structure with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…In the preceding publications, the preparation, characterization, and physical properties of EuCrO 3 and CeCrO 3 were described in detail. Phase purity and morphology of samples were confirmed using X‐ray diffraction, neutron powder diffraction, transmission electron microscopy, and scanning electron microscopy. In order to study the surface of particles, XPS measurements were performed on Kratos ESCA AXIS ULTRA spectrometer, equipped with a hemispherical electron energy analyzer and the monochromatic X‐ray source of Al K α (1486.58 eV) under 5× 10 −9 mbar, at the Max Planck Institute for Solid State Research, Germany.…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…In the preceding publications, the preparation, characterization, and physical properties of EuCrO 3 and CeCrO 3 were described in detail. Phase purity and morphology of samples were confirmed using X‐ray diffraction, neutron powder diffraction, transmission electron microscopy, and scanning electron microscopy. In order to study the surface of particles, XPS measurements were performed on Kratos ESCA AXIS ULTRA spectrometer, equipped with a hemispherical electron energy analyzer and the monochromatic X‐ray source of Al K α (1486.58 eV) under 5× 10 −9 mbar, at the Max Planck Institute for Solid State Research, Germany.…”
Section: Methodssupporting
confidence: 71%
“…In the preceding papers, we confirmed the pure distorted orthorhombic structure of EuCrO 3 and CeCrO 3 nano‐powders (with P b n m space group) while our magnetic studies revealed the existence of the canted antiferromagnetic core surrounded by a thin layer of the spin disorder structure, which has inspired us to analyze the surface of particles.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The displacement of the Raman frequencies between Т N and Т * assumes a competition between weak ferromagnetism and antiferromagnetic interaction. Such anomalous behaviour of phonon modes is also observed in EuCrO 3 [18]. In the Raman spectra of RCrO 3 , when R is non-magnetic (Y , La, Lu and Eu), two typical behaviours are observed: 1) below Т N the energy of the phonon mode first increases as around Т * there is a "kink" with additional hardening of the mode and subsequent saturation at very low temperatures; 2) below Т N the energy of the phonon mode first decreases, as around Т * there is a "kink" with an additional frequency increase and subsequent saturation at very low temperatures.…”
Section: +mentioning
confidence: 59%
“…In the situation of K s having opposite signs, easy-cone type anisotropy [59] is expected for K 2 = − 1 2 K 1 to K 2 = ∞ (with K 1 negative), which is practically realized as canted spins [60]. It has been theoretically shown [61] and investigated through microwave spectroscopy studies [62,63] that the SRPT arises due to fourth-order magnetic anisotropy, which is generally small but dominates the orientational behavior when the second-order magnetic anisotropy changes sign [8,64,65].…”
Section: (A) and 5(b)mentioning
confidence: 99%